Bone graft incorporation after revision hip arthroplasty in patients with rheumatoid arthritis, seventy eight revisions using bone allografts with or without metal reinforcements - Kowalczewski, Jacek B. (Springer-Verlag, 2013)
PURPOSE: The aim of the study was to assess bone graft incorporation after revision hip arthroplasty in patients with rheumatoid arthritis (RA). METHODS: We report an acetabular reconstruction using impacted, morselized, frozen, radiation sterilized bone allografts in 71 patients suffering from RA. There were sixty-six women and five men at a mean age of 57.5 years. Reconstruction was performed in 78 revision total hip arthroplasties (THAs) for aseptic loosening of acetabular component. The mean follow-up was five years and four months. In 38 cases, a revision was done with use of reinforcement devices. RESULTS: In four revised hips (10 %) without reinforcement implants, resorption of the allografts was noticed. All Mueller rings and 50 % of unscrews cages (Link, Howmedica) were revised because of aseptic loosening and bone graft resorption. In all of 17 hips with the Burch-Schneider cage, no measurable migration or bone allografts resorption occurred. There were no major general complications. CONCLUSIONS: Acetabular reconstruction with use of morselized, frozen, radiation sterilized bone allografts and the Burch-Schneider cage can be highly successful in managing massive deficiency of acetabular bone stock in revision hip arthroplasty in RA patients.